DAMPAK PEMANFAATAN E-COMMERCE PADA KINERJA UMKM - Chrisnanda Kurnia Putranto; Utpala Rani (Transpublika Publisher, 2022)
The research that the researcher uses aims to determine the effect of the use and utilization of the e-commerce marketing system on the performance of MSMEs. One of the methods that researchers use is descriptive qualitative method. This method uses data collection techniques which include observation, documentation, and interview techniques. The subject of this research is 1 MSME actor who has 3 branches in Magelang City. This study shows that there are two impacts or influences from the use or utilization of e-commerce marketing systems, namely positive impacts and negatif impacts. The positive impact of this business can be accessed anytime and anywhere, and provides convenience in the transaction process. Another positive influence is that it can make it easier to do promotions, so that it can help the communication system with customers more effectively. In addition, it can also access the global market which of course can increase turnover from sales. The negatif impact or influence is that if the goods ordered are damaged, or not in accordance with the wishes of the consumer, the MSME is given a bad rating. of course it will harm the store or MSME.